Factors influencing consumers shopping intention towards online retail shopping in Iloilo City - Batislao, Shineth Ann B.; Hubag, Pauline Grace A.; Tabol, Mark Ivan C.; Togonon, Janelle Rae G.; Velez, Angeline Anne D.; Villarin, Krisleen Joy L.
According to UCLA Center for Communication Policy (2001), online shopping has become the third most popular internet activity, immediately following e-mail using instant messaging and web browsing. With its continued growth, it has become an integral part of everyone's life. With the growth of online shops, most researcher suggest the need to study consumer behavior regarding his/her intention to shop online for it may be fundamentally different from that in the traditional shopping environment. By understanding how factors such as consumer demographics, Internet experience, normative beliefs, innovativeness, shopping motivation, social media, shopping orientation, online shopping experience, and satisfaction affect consumer's online behavior and how these factors affect each other are the objectives of this study. The researchers used the Online Shopping acceptance Model (OSAM) by Zhou, Dai, and Zhang (2007). The study employed a quantitative approach to present a comprehensive description and evaluation of the factors influencing consumer shopping intention towards online retail shopping in Iloilo City. Also, it used measures of central tendency and Structural Equation Modelling (SEM) in analyzing the different variables and their relationships to each other. Results have shown that shopping motivation; social media; perceived outcome; Internet experience through shopping motivation, social media, online experience and perceived outcome; age through shopping orientation and shopping motivation; income through shopping motivation; and culture through normative beliefs, innovativeness, and perceived outcome. by understanding the factors that influence the behavior of online shoppers in Iloilo City, online shops can use this information to design strategy that attract customers to shop online, increase the potential customers interest level, stimulate their desire to buy the products and services, initiate the purchase of product/service and develop loyalty and trust to the customers.